The female gymnast: current concepts in sports medicine - Hutchinson, M. R.; Benardot, D.; Balague, G. (1999)
Over the past few decades, the athletic participation of females in organized sport has expanded dramatically. Growing numbers of female athletes have been able to experience the broad range of health and social benefits that sport participation fosters. A model of this growth can be seen in gymnastics which has seen tremendous expansion since the days Olga Korbut walked the balance beam. Scientific studies evaluating medical, psychological, and nutritional risks and benefits of athletic and, in particular, gymnastic participation for females have shown significant variation between male and female athletes. The purpose of this symposium if to provide a format to present the current concepts of sports nutrition, sports psychology, and sports medicine as they relate to the female gymnast and to allow a forum for discussion of these concepts. - M. R. Hutchinson: Gymnastics and the female athlete - D. Benardot: Energy balance in gymnastics: Conflicting issues of weight, growth, injuries, and performance. - G. Balague: Current concepts: Psychological issues in elite